CITY BRANDING DENGAN KATA DAN AKRONIM: TINJAUAN SEMIOTIKA TERHADAP MAKNA DAN IMPLEMENTASI “RATU” DI KABUPATEN TANGGAMUS - Adib Sofia (Jurnal Studi Komunikasi dan Media, 2023)
Tanggamus Regency has strengths in agriculture, plantation, and tourism sectors. However, the district government has chosen the word RATU for city branding instead. Therefore, the purpose of this paper is to reveal the meaning and implementation of the word. The theory used in this paper is Peirce’s semiotics, which reveals the sign, object, and interpretant. This paper also uses the perspective of city branding in conducting the analysis. There are three things obtained in this study. First, as a sign, the word RATU exists in various public spaces in Tanggamus Regency in the form of product labels, locations, and programs. Second, as an object, the word RATU has different meaning references, but the most common ones are R (Ramah/Friendly), A (Amanah/Trustworthy), T (Tegas/Firm), and U (Unggul/Superior). Third, as an interpretant, this word means the most excellent service in community service sector. The concept of RATU has not been fully linear yet with the strengths, potentials, and identity of Tanggamus Regency that the community has understood.